Absolute Configuration and Antimalarial Activity of erythro‐Mefloquine Enantiomers. Issue 7 (21st June 2013) - Dassonville‐Klimpt, Alexandra; Cézard, Christine; Mullié, Catherine; Agnamey, Patrice; Jonet, Alexia; Da Nascimento, Sophie; Marchivie, Mathieu; Guillon, Jean; Sonnet, Pascal
<x xml:space="preserve">Abstract</x> Mefloquine (MQ), an antimalarial drug, is used as a racemate of (−)‐ and (+)‐enantiomers, which display biological differences. The question concerning their exact configuration remains a matter of debate. The absolute configuration of the two MQ enantiomers as well as their biological activity has been established, thus confirming the importance of the stereochemistry in the design of MQ analogues that have fewer adverse side effects (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>